In-Silico Studies of Musa balbisiana Colla with Proteins Promoting Antibiotic Resistance in Bacterial and Fungal Pathogens - Ramdhani, Danni; Kusuma, Sri Agung Fitri; Kusmiati, Meti (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Fruit of klutuk banana (Musa balbisiana Colla) has been used by Indonesian people to stop the diarrhea caused by the effect of dysentery and also fungal infections of the skin. In this study, we used molecular docking methods to investigate the mechanism of inhibition of their main bioactive compounds cholesta-5,7-dien-3beta-ol, cycloartenol, cyclomusalenone and were compared with the native ligand (the control drugs: amphotericin B, erythromycin and fluconazole) against the proteins responsible for antibiotic resistance in bacterial and fungal pathogens. The target receptor that plays a role were cytochrome P450 14-alpha-sterol demethylase (CYP51), N-myristoyl transferase (NMT), and penicillin-binding protein 3 (PBP3). Swiss ADME servers were used for the determination of Lipinski rule of 5, and drug-likeness prediction respectively, whereas, admetSAR and Protox-II tools were used for toxicity prediction. Cyclomusalenone performed the best binding affinity value -6.0, -8.5, and -6,1 (kcal.mol-1) compared than the control drugs (amphotericin B, erythromycin, and fluconazole). All the bioactive compounds are non-carcinogenic and non-cytotoxic by nature, and they all conform to the Lipinski rule. Based on these data, we recommend predicting the targets of bioactive compound for testing antifungal activity in vitro and in vivo.